Digital Public Service Evaluation in Brazil: Federal Managers’ Perspectives and Improvement Opportunities - Pedrosa, Glauco V.; Canedo, Edna Dias; Pereira, Wander; Figueiredo, Rejane M. da C. (Anais do Latin American Symposium on Digital Government (LASDiGov); 2025: Anais do XIII Latin American Symposium on Digital Government, 2025)
This study explores the challenges and perceptions of federal public managers regarding the current evaluation system for digital public services in Brazil. Through two focus groups conducted with 20 managers from 11 public institutions, the main difficulties in using the existing evaluation system were identified, along with potential adjustments to enhance its effectiveness. The focus group discussions generated various recommendations for improving the system’s efficiency and usability, including increasing the visibility of the evaluation function, automating data collection and analysis, and clearly distinguishing between the evaluation of customer service and the overall service itself. This work provides a structured account of the focus group discussions and offers recommendations based on these insights, aiming to improve the delivery of digital public services by making them more efficient, transparent, and user-centered.